Mobile Application for Data Acquisition in Integrated Forest and Land Fires Patrols - Dhani Sulistiyo Wibowo; Imas Sukaesih Sitanggang; Ikhsan Kurniawan; Wulandari (Graduate School Bogor Agricultural University (SPs IPB), 2021)
Hotspot is one of the indicators of forest and land fires which is usually checked in the field through an integrated patrol program by a team formed by the Ministry of Environment and Forestry (KLHK). The findings from these patrol activities are usually reported through texts posted in the chat group media using the WhatsApp application. This method is, however, considered ineffective in presenting information queries from the patrol data. Therefore, this research aims to develop a mobile application to record data retrieved during forest and land fire patrols in the Sumatra region. The prototyping system development method was applied and this includes analyzing the needs of the user, designing and modeling the prototype, coding the system, testing the system, and system usage. Moreover, the Ionic 3 framework was employed in the system development through the application of the API from the back-end module. The application was integrated into the Google Maps Application Programming Interface (API) and the system was tested using the Blackbox method to show the features in the system function effectively.